Efficacy of antepartum administration of hepatitis B immunoglobulin in preventing mother‐to‐child transmission of hepatitis B virus. Issue 9 (3rd June 2019) - Zhao, Mengyu; Zou, Huaibin; Chen, Yu; Zheng, Sujun; Duan, Zhongping
Abstract: The aim of this study was to investigate the efficacy of antepartum administration of three doses of hepatitis B immunoglobulin (HBIG) in interrupting mother‐to‐child transmission (MTCT) of hepatitis B virus (HBV). In this trial, a total of 728 HBeAg‐positive pregnant women with chronic HBV infection who had an HBV DNA level higher than 6log10 copies/mL were enrolled. They were divided into three groups based on individual preference. Subjects in group A and group B received 200 IU (unit) HBIG and 400 IU (unit) HBIG intramuscularly once a month at the third, second and first month before delivery, respectively. Subjects in the control group (C) received no special treatment. All the infants received passive‐active immunoprophylaxis. The HBsAg‐positive rate of all infants at 7‐12 months of age was 5.1% (37/728). Specifically, the HBsAg‐positive rate of infants was comparable in all three groups (5.3% vs 5.1% vs 5%, P = 0.988). No significant difference was found in anti‐HBs levels between the infants aged 7‐12 months in the three groups ( P = 0.469). HBV DNA levels of the umbilical cord blood in the HBV‐infected group were higher than those in the uninfected group (5.2 vs 3.4log10 copies/mL, P < 0.001), and these with family history of HBV infection were also higher (45.9% vs 28.5%, P = 0.034). To conclude, administration of passive‐active immunoprophylaxis to infants contributed to effective prevention of the MTCT of HBV; extra antepartum administration of HBIG during pregnancy could not decrease the rate of MTCT or increase the anti‐HBs levels of infants born to HBsAg‐positive mothers with HBV DNA higher than 6log10 copies/mL.